2016
DOI: 10.1007/s11248-016-9928-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetically engineered livestock for biomedical models

Abstract: To commemorate Transgenic Animal Research Conference X, this review summarizes the recent progress in developing genetically engineered livestock species as biomedical models. The first of these conferences was held in 1997, which turned out to be a watershed year for the field, with two significant events occurring. One was the publication of the first transgenic livestock animal disease model, a pig with retinitis pigmentosa. Before that, the use of livestock species in biomedical research had been limited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 89 publications
0
28
0
Order By: Relevance
“…Genetic analysis fully confirmed the clonal origin of the monkeys generated by SCNT. This study demonstrated that cloning of non-human primates is feasible by SCNT using fetal somatic cells, which could be efficiently modified by genetic editing and screening in vitro (Gao et al, 2017;Lai et al, 2016;Rogers, 2016). Such cloning allows the production of genetically uniform monkeys as animal models for basic research in primate biology and for studying human disease mechanisms and therapeutic treatments.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Genetic analysis fully confirmed the clonal origin of the monkeys generated by SCNT. This study demonstrated that cloning of non-human primates is feasible by SCNT using fetal somatic cells, which could be efficiently modified by genetic editing and screening in vitro (Gao et al, 2017;Lai et al, 2016;Rogers, 2016). Such cloning allows the production of genetically uniform monkeys as animal models for basic research in primate biology and for studying human disease mechanisms and therapeutic treatments.…”
Section: Discussionmentioning
confidence: 93%
“…Monkey neonates generated using fetal fibroblasts were healthy, whereas those generated using adult cumulus cells survived only briefly after birth. Since fetal fibroblasts could be genetically modified efficiently in vitro and properly screened for precise gene editing (Gao et al, 2017;Lai et al, 2016;Rogers, 2016) prior to SCNT, our results pave the way for the generation of genetically uniform monkey models for basic research and biomedical applications.…”
Section: Introductionmentioning
confidence: 87%
“…In addition, genome editing is non-trivial in large animals, whose importance in the provision of biomedical models and clinical reagents (eg for xenotransplantation) is increasing (46). By streamlining safe target locus homogenotization (ie allelic replacement…”
Section: Discussionmentioning
confidence: 99%
“…The biomedical toolbox for pigs has heavily increased during the last decade leading to its strongly increased popularity as a model for biomedical research and especially for preclinical vaccine studies (Gerdts et al, 2015;Meurens et al, 2012). Over the past ten years, many excellent reviews have been published related to the potential and documented success of the pig as a biomedical model for conditions in humans (Fairbairn et al, 2011;Gerdts et al, 2015;Klymiuk et al, 2016;Meurens et al, 2012;Rogers, 2016;Rogers et al, A C C E P T E D M A N U S C R I P T 5 2008). Various studies that utilized the swine model for the study of human infectious diseases with significant contributions and potential new developments were reviewed by Meurens et al (Meurens et al, 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Pigs have also been used as a preclinical models to decipher complex human diseases, and to accelerate the development of safe and efficient therapies (Klymiuk et al, 2016;Schomberg et al, 2016). The recent development of gene editing tools further increases the potential of large animals, including pigs, to model human diseases as presented in some interesting reviews (Rogers, 2016;Whitelaw et al, 2016).…”
Section: The Pig As a Model In The Study Of Human Sexually Transmitedmentioning
confidence: 99%